(3EVGAI GdQGehS hEVGaI GdfGehS Ydi EVGAI GdbGehSs - (3eMeO Hf GdWjH eMeO Hf eMeO Hf eMeO GdTQbj GdaGSj GdeGdcj, CHh YHO Gddg , J (B1170 (3g`s; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3BNQgG (B:s
(3ef aUd GdjGA(B( (3ef HGH GdLje (B) (3, bhdg (B: (3bdJ (B: (3hcCfg de jYQH GfJgi HGH GdLje HMeO Gddg , hjdjg HGH GdMGA GdegedI , hGddg Gdehab ddUhGH s
(3HgG fXGe GdJYbjHIs
(3JJab ai ChdgG eY Chd fSNI GdNRGfI GdedcjI (B_ (3GdQHGW (B1/ 544 (3HGNJdGa jSjQ ai HYV GdCdaGXs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B23 s
Keywords: (3GddZIs